A clinical case of adult-onset Still's disease resistant to therapy with tumor necrosis factor-alpha inhibitors and interleukin-6 inhibitors - R. R. Samigullina; E. A. Vasilenko; V. I. Mazurov (Современная ревматология, 2019)
The basis of the clinical picture of adult-onset Still's disease is a triad of symptoms, includingfever, arthralgia/arthritis, and characteristic rash called «Still rash». The first line of therapy includes glucocorticoids, synthetic disease-modifying anti-rheumatic drugs; biological agents, such as tumor necrosis factor a inhibitors and interleukin-6 and interleukin-1 inhibitors, are used in standard therapy-resistant cases.